The Role of Social Engineering in the Rehabilitation of Drug Addicts: A Legislative Analysis of Indonesia's Drug Policy Framework - Wredha Danang Widoyoko; Siti Ngaisah; Haryono Haryono; Diah Ayu Rahmawati; Yoga Adi Prayogi (Westscience Press, 2024)
This study examines the role of social engineering in the rehabilitation of drug addicts within Indonesia’s drug policy framework through a normative juridical analysis. The research evaluates legislative provisions, such as those outlined in Law No. 35 of 2009 on Narcotics, focusing on their alignment with social engineering principles and their effectiveness in achieving rehabilitation and reintegration. Findings reveal that while Indonesia's policies incorporate rehabilitative elements, challenges such as limited resources, inconsistent judicial practices, and societal stigma hinder optimal implementation. Comparative insights from countries like Portugal and Switzerland demonstrate the potential of adopting harm reduction and public awareness strategies to enhance outcomes. This study underscores the need for a more integrated, inclusive policy approach to strengthen Indonesia’s rehabilitation framework, reduce stigmatization, and promote sustainable recovery.